Cholangiocarcinoma: Experience of Srinagarind Hospital - Bhudhisawasdi, Vajarabhongsa; Khuntikeo, Narong; Chur-in, Siri; Pugkhem, Ake; Talabnin, Chutima; Wongkham, Sopit (ศรีนครินทร์เวชสาร, 2013)
Cholangiocarcinoma (CCA) arises from intra- andextra-hepatic biliary epithelial cells. The incidence of CCAis low worldwide, however, it is very high in the northeasternpart of Thailand especially in Khon Kaen province. Mostof patients presented tumor at late stage with large tumorsize and almost always metastasized to local and distantorgans. CCA can be subgrouped according to the tumorappearance into mass-forming, periductal infiltrating andintraductal growth. Based on the retrospective recordsof 181 intrahepatic CCA cases operated at SrinagarindHospital, Faculty of Medicine, Khon Kaen University duringB.E. 2541-2545, 73% were mass-forming type, theaverage age was 56 years, male: female = 2.2: 1, and only10 cases (5.5%) were peri-operative death. The mediansurvival was 224 days (95% CI; 160-287 days). Factorsthat offered the long survival of patients were intraductalgrowth type, R0 resection, early stage tumor and completechemotherapy treatment after surgery. This study indicatesthat even surgery is the only curative treatment for CCA,however, it will be effectively based on tumor type, tumorstage, R0 resection and complete chemotherapy treatmentafter surgery. Keywords : bile duct cancer, surgery, prognosis,chemotherapy